2006
DOI: 10.1097/01.tp.0000228867.98158.d2
|View full text |Cite
|
Sign up to set email alerts
|

Liver Regeneration Is Suppressed in Small-for-Size Liver Grafts after Transplantation: Involvement of c-Jun N-terminal Kinase, Cyclin D1, and Defective Energy Supply

Abstract: Liver regeneration is stimulated in half-size grafts but suppressed in quarter-size grafts. Defective liver regeneration in small grafts is associated with an inhibition of the c-Jun N-terminal kinase/c-Jun and CyD1 pathways and compromised energy production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 54 publications
5
97
0
Order By: Relevance
“…Tissue damage due to the surgical process further decreases the amount of healthy remnant liver tissue leading to an additional reduction in functional liver capacity in the postoperative period [4,5] . This situation can lead to liver insufficiency and, ultimately, to liver failure and death [6][7][8] . Therefore, patients have to fulfil certain criteria, such as the absence of end-stage liver disease, in order to be eligible for extended hepatectomy [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue damage due to the surgical process further decreases the amount of healthy remnant liver tissue leading to an additional reduction in functional liver capacity in the postoperative period [4,5] . This situation can lead to liver insufficiency and, ultimately, to liver failure and death [6][7][8] . Therefore, patients have to fulfil certain criteria, such as the absence of end-stage liver disease, in order to be eligible for extended hepatectomy [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the initiating events in AILI have been attributed to reactive metabolite and protein adduct formation as well as glutathione depletion [2][3][4], the downstream signaling pathways controlling or promoting the severity of AILI have become of a great interest to many researchers [5][6][7][8][9][10][11][12][13][14]. One of these pathways involves JNK, which when activated is known to influence important cellular events, including alterations in gene expression [15], cell death [16], cellular proliferation and survival [17][18][19][20].Recent studies involving AILI in JNK2 −/− mice have led to conflicting results where JNK2 −/− mice were found to be either less susceptible [21] …”
mentioning
confidence: 99%
“…After resection or injury the remaining hepatocytes enter into the G1 phase. Several previous studies demonstrated that cytokines, mainly TNF-α and IL-6, are involved in liver regeneration after partial hepatectomy [1,6,10,25] . TNF-α is recognized as a regulator of the initial phase of hepatic regeneration after liver resection and injury, given that it is able to increase the activity of DNA polymerase-α and the incorporation of [H3] thymidine into DNA in the liver cells of intact adult rats [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Liver regeneration in small-for-size liver grafts and in subtotal hepatectomies may be suppressed, thereby increas-ing the morbidity and mortality in these situations [1,2] . The regenerative capacity of the liver has been known for a long time although the mechanisms of this complex physiological process are not completely understood.…”
Section: Introductionmentioning
confidence: 99%